Exploring the role of innovation and entrepreneurship in environmental sustainability：Evidence from GBA Cities in China - Ma, Mu-Han (Journal of Innovative Studies, 2020)
While the role of innovation and entrepreneurship is expected to benefit environmental sustainability, the effects are not consistent along the periods of economic development and enterprise life stages. This research studies in which stage and to what extent, innovation and entrepreneurship affects environmental sustainability of cities in Greater Bay area (GBA), China. The method of Gini coefficient and spatial autocorrelation are used to describe the evolutionary characteristics of innovation and entrepreneurship index (IEI) and environment index (EI) along time and space. And the model of STIRPAT is used for regression test to find out the relationship between these variable. The findings of this study suggest that in the previous stage of economic development, the factor innovation and entrepreneurship plays no significant role in sustainable environment. When the economy goes to the fast developing stage, this role becomes negative. When the natural resources become the main constraints of development and pressure from society increases, the effects of innovation and entrepreneurship change to be less negative and are expected to be positive. This study contributes to the theory of sustainable innovation and entrepreneurship, and provides experience to the policy maker.